Association between speech rate measures and cognitive function in people with relapsing and progressive multiple sclerosis. Issue 3 (July 2022) - O'Keeffe, Clodagh; Yap, Siew Mei; Davenport, Laura; Cogley, Clodagh; Craddock, Fiona; Kennedy, Alex; Tubridy, Niall; Looze, Céline De; Suleyman, Narin; O'Keeffe, Fiadhnait; Reilly, Richard B.; McGuigan, Christopher
Background: Cognitive impairments are well-documented in multiple sclerosis (MS), while speech impairments are often overlooked despite their significant effect on quality of life. For effective clinical management of multisystem conditions such as MS, consideration should be given to the interaction between deficits in multiple domains, such as speech and cognition. To evaluate speech rate measures of spontaneous and read speech, in people with MS and to examine the link between speech and cognition. Methods: Forty-five people with MS and 25 controls underwent an extensive cognitive battery, including executive functioning, information processing and memory tasks, and completed two speech tasks: a reading task and a picture description task, from which speech rate measures were derived. Results: The progressive MS cohort had reduced articulation ( p < 0.04) and speech rate ( p < 0.02) compared to controls and those with relapsing MS. Regression models also revealed information processing speed accounted for 18% to 30% of the variance of spontaneous speech rate measures, and 27% of read speech. Executive functioning accounted for a further 10% of the variance of speech rate in those with MS. Conclusions: The present study suggests that speech production is contingent on cognitive ability, with information processing speed and executive functioning linked with speech timing patterns.